Paediatric cochlear implantation factors that affect outcomes. (January 2017) - Driver, Sandra; Jiang, Dan
Abstract: Cochlear implantation is an established surgical intervention for individuals with bilateral severe to profound sensorineural hearing loss. The aim of the interevention is to provide the individual with a sensation of sound which they can learn to interpret with meaning. Outcomes vary considerably and the factors that impact on outcomes will be discussed.